Characterization of Streptococcus pneumoniae invasive serotype 19A isolates from Argentina (1993–2014). Issue 35 (16th August 2017) - Gagetti, Paula; Faccone, Diego; Reijtman, Vanesa; Fossati, Sofia; Rodriguez, Marisa; Veliz, Omar; Ceriana, Paola; Regueira, Mabel; Corso, Alejandra
Abstract: The aim of this study was to characterize Streptococcus pneumoniae serotype 19A isolates causing invasive pneumococcal disease in children, collected in Argentina between 1993 and 2014. A total of 176 isolates serotype 19A were analyzed. There was an increase in the proportion of serotype 19A isolates from 3% in 1993 to 6% in 2011, prior to the introduction of PCV13 in 2012, and from 2012 to 2014 its proportion gradually decreased. Penicillin resistance among serotype 19A isolates throughout the study period was 65.9%, but a significant increase was observed from 0% in 1993 to 87.5% in 2014. Genetic relationship of the isolates was determined by PFGE and selected strains were studied by MLST. Most of the isolates belonged to two clonal types: A (54.5%) and B (11.4%). Isolates of clonal type A were ST1131, a single locus variant of ST172 and accounted for 54% of the total collection. They were detected for the first time in our country in 1997 and most of them (93%) were penicillin non susceptible. Isolates of clonal type B were ST8121, a single locus variant of ST199, and were mainly susceptible to penicillin. These two clonal types are still in circulation and appear to be responsible for the dissemination of S. pneumoniae serotype 19A invasive isolates in our country.